230k views
5 votes
Suppose that F(x) = f(g(x)) where g(3)=6, g(6)=13, g'(3)=4, g'(6)=2, f(3)=11, f(6)=15, f'(3)=4, and f'(6)=8. Find F'(3).

User Jafin
by
5.9k points

1 Answer

4 votes

The rule for deriving composite functions (known as the chain rule) is:


(f(g(x))' = f'(g(x))\cdot g'(x)

So, in your case, we have


F'(3) = f'(g(3))\cdot g'(3)

We know that
g'(3) = 4 and
g(3)=6

So, the expression becomes


F'(3) = f'(6)\cdot 4

Finally, since
f'(6)=8, we have


F'(3) = 8\cdot 4 = 32

User Nize
by
5.5k points